Interaksi Kampung Kuliner Wisata Mas Kelurahan Nunu - Alfaiz, Abdul Khalik (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
In the process of interaction between the Kaili and Javanese people, it requires harmonious social relations with the living conditions of individuals and groups who live in line with community members who live their respective natures marked by solidarity and harmony in societies that have different cultures. This study aims to determine the interactions that occur between the Kaili and Javanese people in the